Christology in cultural perspective marking out the horizons - Greene, Colin J.D. (Carlisle, UK Paternoster, 2003)
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- history of doctrines; Christianity and culture -- Europe -- history